Tantangan Pelaksanaan Program Seleksi Terbuka Jabatan Pimpinan Tinggi (JPT) Pratama di Kota Lhokseumawe - 12, Zahniar; Nazaruddin, M.; Abubakar, Muhammad Bin (Jurnal Transparansi Publik (JTP), 2022)
There were issues with the open and Assessment Center-based process used to fill the Primary High Leadership Position (JPT) in Lhokseumawe City in 2018. Political interference was still very strong, and there were still likes and dislikes (and dislikes), so the selection of ASN for the Primary High Leadership Position did not follow the merit system based on competence, education, and experience (merit system). Descriptive and qualitative research methodologies are used in the study of the Primary High Leadership Position (JPT) selection analysis in the Lhokseumawe City Government. Many employees who find it challenging to participate in the position auction or open selection are among the obstacles that are experienced. been untested. Each apparatus only possesses a small amount of leadership spirit, which has an impact on how employees behave when they aren't competitive enough to compete in a succession of job auction selection processes before particular positions become open. The provision of additional resources, specifically the budget for facility and infrastructure upkeep, is necessary to assist the Lhokseumawe City Government's success in supplying human resources and infrastructure.